SOCIALIZATION COMMUNICATION ROLE OF TEACHERS AND PREVENTION OF TEENAGE PREGNANCIES IN PUBLIC SECONDARY SCHOOLS IN NAROK COUNTY, KENYA - Miriti, Purity; Mberia, Hellen; Wa Ngula, Kyalo (International Journal of Communication and Public Relation, 2021)
Purpose: The purpose was to assess the socialization communication role of teachers and prevention of teenage pregnancies in public secondary schools in Narok County, Kenya. Methodology: A mixed research design was used in the study. The population of the study included all the 8994 female students of Narok County from 52 secondary schools in the Narok County in the year 2019. The respondents were aged between 13-19 years attending both boarding and day public secondary schools in Narok County in both. Stratified technique of sampling was used to sample the population into strata. The study selected proportionally the subjects from different strata. Total study sample size was 536; 500 respondents for the questionnaire, 12 for the interview, and 24 for the focus group discussions. A questionnaire, key informant interviews and focus group discussions were used to collect data. Quantitative data was analyzed using Statistical Package for Social Sciences computer software package (SPSS statistics version 22). Descriptive statistics drawn include mean, and standard deviation which were presented in tables, frequencies and percentages. Inferential statistics drawn include multiple regression and correlation analysis. Findings: A significant majority (86.3%) of the respondents indicated that teachers advise on teenage pregnancy impacts positively on student behavior while the rest indicated that it impacted negatively Unique Contribution to the Society, Policy and Theory: The findings of this research showed that socialization communication helps prevent teenage pregnancies. This therefore means that girls would be able to complete school advance in their studies and when they eventually are of age and ready for marriage, they can help alleviate vicious cycle of poverty as they are eligible to formal employment. There will be general growth in society as women will be empowered. The government and stakeholders should strengthen policies and enhance initiatives to educate more girls and reduce early marriages to the elders in the society, to socialize teenagers in the reality of modern life and the challenges that result in teenage pregnancies. The study improves the theory in that it connects socialization to the role of the teacher